Development of a Letter and Basic Calculation Learning Application for Grade 1 Students at SDN Kapuk Jaya Using Construct 2 - Rohman, Ali; Nugroho, Nurhasan; Munawir, Ahmad; Pratama, Gelard Untirtha; Badruzzaman, Ahmad Jibril (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to design and develop an application for letter recognition and basic arithmetic for first-grade students at SDN Kapuk Jaya using Construct 2. The application is designed to help increase students' interest and motivation in learning through interactive and enjoyable learning methods. The research method used is Research and Development (R&D), which involves several stages: research and information gathering, planning, initial product development, preliminary field testing, product revision, main field testing, final improvement, and implementation. The results show that the application is effective in enhancing students' understanding of letters and basic arithmetic. Additionally, the application received positive feedback from teachers and students, who found that it facilitated the learning process and made it more engaging. Therefore, this application is expected to be an effective teaching tool in the first-grade classroom.